Nonlinear behavior of reinforced concrete shear walls with various openings - Aryasatya, Muhammad Maheswara; Sukrawa, Made; Sudarsana, I Ketut; Putra, Putu Ryandika (Edelweiss Applied Science and Technology, 2025)
This study analyzes the nonlinear behavior of reinforced concrete shear walls with openings using two-dimensional models in SAP2000. The analysis includes two main models—a full shear wall (MV-WS) and a shear wall with reinforced openings (MV-WO)—as well as eight variation models: four with different opening percentages (OV22, OV37, OV52, OV72) and four with varying opening positions (OS, OE18, OE36, OE54). The objective is to evaluate the use of layered shell elements for modeling shear walls with openings and to assess displacement and stress responses due to variations in opening size and location. Validation against experimental load–displacement curves and crack patterns confirmed that the layered shell approach captures elastic behavior effectively, although it is less accurate for plastic responses. The findings show that a lower percentage of openings leads to greater base shear capacity, and that shear strength improves with increased compressed area resulting from optimal opening placement.